Biodegradable polycarbonates containing side carboxyl groups—synthesis, properties, and degradation study. Issue 17 (14th June 2017) - Jaworska, Joanna; Kawalec, Michal; Pastusiak, Malgorzata; Reczynska, Katarzyna; Janeczek, Henryk; Lewicka, Kamila; Pamula, Elzbieta; Dobrzynski, Piotr
ABSTRACT: The main objective of the presented research was to synthesise biodegradable aliphatic polycarbonates containing reactive carboxyl pendant groups and to examine the influence of the copolymer chain microstructure and composition on the process of their hydrolytic degradation and cytocompatibility. The work describes copolymerization of cyclic trimethylene carbonate derivative containing benzyl‐ester pendant group (benzyl 5‐methyl‐2‐oxo‐1, 3‐dioxane‐5‐carboxylate) with trimethylene carbonate. The copolymerization was conducted with the use of zinc (II) and lanthanum (III) acetylacetonates as ring‐opening polymerization coordination initiators. Detailed NMR analysis allowed to define the microstructure of the obtained copolymers, which depended on the composition and type of used initiator. The final tapered chain microstructure of the obtained copolymers was related to huge differences in comonomers reactivity and evidenced low level of transesterification of the main copolymer backbone. Chosen copolymers, with unprotected carbonyl groups, were subjected to in vitro degradation test and cytocompatibility studies. It was found that high concentration of carboxyl groups resulted in copolymers which formed hydrogels and were very prone to hydrolytic degradation; they were also cytotoxic toward osteoblast‐like MG 63 cells. Copolymers with lower content of carboxyl groups were found less susceptible to degradation and cytocompatible with studied cells. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2756–2769 Abstract : This article presents results on the synthesis of aliphatic polycarbonates containing carboxylic side groups. The obtained semicrystalline copolymers containing more than 20% of carboxyl‐functionalized chain unit form hydrogels. Conducted NMR analysis is allowed to determine the chain microstructure of these copolymers and their influence on the rate of hydrolytic degradation. A high content of carboxylic side groups resulted in fast hydrolytic degradation and cytotoxicity of the copolymers, but copolymers with lower concentration of carboxyl groups were found more cytocompatible and less prone to degradation.